Fatores relacionados à hipertensão arterial em mulheres empregadas em uma instituição pública de ensino superior - Goes, Cristina de Sousa Borges (2008)
The recent epidemiological and demographic Brazilian profile demonstrates important changes on the population’s morbidity and mortality standards on the last decades, putting the cardiovasculares diseases as the main cause for death and illness in Brazil. Among the diseases of this group, the arterial hypertension presents the greater prevalence in the morbidity taxes. The risk factors associated to arterial hypertension as obesity, diets rich in fat, excessive ingestion of salt, sedentary lifestyle, smoking and elitism are the most cited on literature. However, social demographic aspects as age and instruction, professional work characteristics and psychosocial aspects at work, are been pointed as important factors on determining the hypertension. The aim of this study was describe the prevalence of the Arterial Hypertension on women employed on a higher education institution, according to social and demographic aspects, professional work characteristics and habits and lifestyle. A cross-sectional study was done with all the technical and administrative women employees and the women from the service provision that were working in 2007. A questionnaire with questions about the social demographic characteristics, habits and lifestyle and professional work characteristics was used. To evaluate the psychosocial aspects at work it was used the Job Content Questionnaire (JCQ). The arterial pressure was checked three times but only the medium of the last two ones was used. For the interpretation and analyses of the data it was used the univariate and multivariate analysis (Analysis of Multiple Logistic Regression – AMLR). 402 employees were evaluated, getting a global prevalence of arterial hypertension of 29,9%. The greater prevalence ratio (PR) or arterial hypertension were found among those with age equal or superior to 40 years old (PR=2,43), those who self-referred black (PR=1,59), low instruction (RP=2,43), small income (PR=1,55), those who have more then two children (PR=4,26) and the smokers (PR=2,35). Among the work characteristics, stands out the workers of the group o general services activities (PR=1,71) and those who started working before they were 15 years old (PR=1,70). The results gotten at the AMLR showed statistically significant association between arterial hypertension and the variables: age, middle and high schooling and those who have children. Making evident the relations between the professions and the diseases, such as arterial hypertension, it will give subsidy so that the ways to promote the workers health can be established, reducing the absenteeism and the missing days of work, and improving their quality of life.